2022
DOI: 10.21203/rs.3.rs-840708/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk Factors for Late Linkage to Care and Delayed Antiretroviral Therapy Initiation Amongst HIV Infected Adults in Sub-saharan Africa: a Systematic Review and Meta-analyses

Abstract: Background: Late linkage to care and delay in antiretroviral therapy (ART) initiation threaten the clinical and public health benefits of ART such as: preventing acquired immunodeficiency syndrome (AIDS) and non-AIDS related morbidities and mortality, as well as reducing new infections. The prevalence of both of these poor care outcomes remains high in sub-Saharan African (SSA) countries. Quantitative synthesises of the existing data are lacking, which would help ascertain the best evidence-based interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(247 reference statements)
0
0
1
Order By: Relevance
“…These results highlight the importance of community-based testing as a strategy to reach men. Age and sex were not significantly associated with early ART initiation, contrasting with findings from a systematic review which found that younger age groups (<35 years old) and being a male were associated with higher risk of delayed ART initiation [26].…”
Section: Discussioncontrasting
confidence: 90%
“…These results highlight the importance of community-based testing as a strategy to reach men. Age and sex were not significantly associated with early ART initiation, contrasting with findings from a systematic review which found that younger age groups (<35 years old) and being a male were associated with higher risk of delayed ART initiation [26].…”
Section: Discussioncontrasting
confidence: 90%